Kajian Sumber Ide dan Makna Simbolis dari Motif Batik â€œMasjid Agung Demak dan Ornamennyaâ€ - Ricfatul Ulum (Syntax Idea)
Batik is one of the cultural heritages that has become the identity of the Indonesian nation. UNESCO (United Nation Educational, Scientific and Cultural) in 2009 determined that batik meets the criteria as a world heritage. Besides being rich in symbols and beauty, batik has a philosophical meaning in the life of the Indonesian people. In this study, the authors aim to examine the sources of ideas and symbolic meanings of the batik motif "The Great Mosque of Demak and Its Ornaments". Techniques for collecting data using observation and interviews. The data that has been collected will be analyzed using a qualitative descriptive technique. The results of the research are expected to increase the interest of the community, especially Demak, about batik in Demak.